(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2017)
Background: Laryngoscopy and tracheal intubation is invariably associated with a reflex sympatheticpressor response resulting in elevated heart rate and blood pressures. This may prove detrimental inhigh risk patients. Many drugs have been suggested in modifying in haemodynamic responses tolaryngoscopy and intubation. Objective: To assess efficacy of two drugs Fentanyl and Lignocaine and to assess which one is moreeffective to attenuate haemodynamic response to direct laryngoscopy and endotracheal intubation. Methods: A total number of 60 patients ASA class I and II were selected randomly as per inclusion andexclusion criteria in two groups, 30 patients in each group. Group F received Fentanyl 1.5mg/kg IV5min before intubation and group L received Lignocaine 1.5mg/kg IV 90 sec before intubation. Peroperativedata were recorded at 1min, 2min, 5min and 10min after intubation. Result: The mean heart rate(HR), systolic(SBP), diastolic(DBP), mean(MAP) arterial pressure and ratepressure product(RPP) before starting anaesthesia were similar in group- F(Fentanyl) and L(Lignocaine).But the values were significantly lower in group F(Fentanyl) at 1, 2, 5 and 10 minute than groupL(Lignocaine). Conclusion: Fentanyl 1.5mcg/kg is superior to Lignocaine 1.5mg/kg for attenuation of haemodynamicresponse (HR, SBP, DBP, MAP and RPP) to laryngoscopy and endotracheal intubation. JBSA 2017; 30(2): 96-101